Determining the Fate of Neurons in SCA3: ATX3, a Rising Decision Maker in Response to DNA Stresses and Beyond - Tu, Yingfeng; Li, Xiaoling; Zhu, Xuefei; Liu, Xiaokang; Guo, Caixia; Jia, Da; Tang, Tie-Shan (Frontiers in Cell and Developmental Biology, 2020)
DNA damage response (DDR) and apoptosis are reported to be involved in the pathogenesis of many neurodegenerative diseases including polyglutamine (polyQ) disorders, such as Spinocerebellar ataxia type 3 (SCA3) and Huntington’s disease (HD). Consistently, an increasing body of studies provide compelling evidence for the crucial roles of ATX3, whose polyQ expansion is defined as the cause of SCA3, in the maintenance of genome integrity and regulation of apoptosis. The polyQ expansion in ATX3 seems to affect its physiological functions in these distinct pathways. These advances have expanded our understanding of the relationship between ATX3’s cellular functions and the underlying molecular mechanism of SCA3. Interestingly, dysregulated DDR pathways also contribute to the pathogenesis of other neurodegenerative disorder such as HD, which presents a common molecular mechanism yet distinct in detail among different diseases. In this review, we provide a comprehensive overview of the current studies about the physiological roles of ATX3 in DDR and related apoptosis, highlighting the crosslinks between these impaired pathways and the pathogenesis of SCA3. Moreover, whether these mechanisms are shared in other neurodegenerative diseases are analyzed. Finally, the preclinical studies targeting DDR and related apoptosis for treatment of polyQ disorders including SCA3 and HD are also summarized and discussed.